Impact of fine particulate matter (PM2.5) on ocular health among people living in Chiang Mai, Thailand - Sobia Kausar; Phanika Tongchai; Sumed Yadoung; Shamsa Sabir; Supansa Pata; Woottichai Khamduang; Kriangkrai Chawansuntati; Supachai Yodkeeree; Anurak Wongta; Surat Hongsibsong (Scientific Reports)
Abstract Considering the limited information on the impact of PM2.5 content on ocular health, a follow-up study was conducted on 50 healthy adults. Samples were collected twice, once before the PM2.5 exposure season and again after exposure. Daily PM2.5 concentration data was gathered from Thung Satok monitoring station. All subjects completed the self-structured ocular symptom questionnaire. The concentrations of 1-OHP were determined using HPLC-FLD. Logistic regression analysis investigated the relationship between PM2.5 toxicity and ocular symptoms. The findings revealed that daily PM2.5 concentrations surpassed the WHO-recommended range by around threefold. Exposure to PM2.5 significantly raised the likelihood of ocular redness (adjusted OR: 12.39, 95% CI), watering (adjusted OR: 2.56, 95% CI), and dryness (adjusted OR: 5.06, 95% CI). Additionally, these symptoms had an exposure-response relationship with increasing 1-OHP levels. Ocular symptoms worsened in frequency and severity during the high PM2.5 season, showing a strong link to elevated PM2.5 levels. Lymphocyte counts were also positively correlated with redness, watering, and dryness during high PM2.5 exposure. In conclusion, our study shows that subjects exposed to higher PM2.5 levels presented more significant ocular surface alterations.